Fragment reconstruction and ancestry estimation of skulls using 3D models - Menezes, Luís Pedro Leitão (2018)
In archaeological sites, it is common to find fragmented human osteological remains, namely skulls. The main goal of this dissertation is to investigate processes to create reconstructions using three dimensional models(3D) in order to allow the study of fragmented skulls. This work also aims to improve the application CraMs, Craniometric Measurements, by adding new functionality to reassemble skull fragments and expanding the ancestry classification using statistical analysis. This application was initially developed in the context of a Master dissertation with the goal of assisting the anthropologist’s work in performing craniometric measurements and by using 3D models of the individuals reduce the variability in the measurements obtained by the different specialists while at the same time contributing to the preservation of the specimens. The work developed in this dissertation is focused on the reconstruction of specimens that are in a fragmented state to be later analyzed with CraMs, something which was not previously possible. Methods were also developed to allow for a centralized storage of previous analysis by anthropologists and use them to estimate the ancestry of an individual using statistical analysis.